Study on Inhaler Spacer Using ESD-Safe Material - BIN MAKLARIN, ANWAR MAHMUD; Binti Asmuin, Nor Zelawati (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The aim of this thesis is to perform study on the ESD-safe 3D printing material that can be used for inhaler spacers when compared with other available 3D printing material that are available commercially. The study on ESD-safe characteristics of 3D printing material have been done in the form of study of electrical properties and triboelectric quantification, but the material that were covered by previous study is limited. Most studies done before also focuses more on the application of the material in electrical and mechanical engineering and not on medical application such as for the usage for the fabrication of inhaler spacers. This study will focus more on how accumulation of charge differs between different 3D printing material, which is PLA and ABS material, as well as the fabrication method used in the terms of infill patterns and infill densities. Experimentation done shows that the accumulation of charge only differs with the material, with the infill patterns and densities having little to no effect on the findings. The finding shows that after triboelectric charging, ABS material accumulates no electrostatic charge while PLA material still accumulate a small amount of it indicating that the ABS material is the best material to be used for the fabrication of the inhaler spacer. This shows that when the electrostatic discharge characteristic of a product is being considered, the selection of material is more important when fabricating it using 3D printing, especially for medical purposes.